SCIENTIFIC-PEDAGOGICAL HERITAGE OF THE ACADEMICIAN S.U. GONCHARENKO AND ITS INFLUENCE ON THE DEVELOPMENT OF RESEARCH ON THE PROBLEMS OF THE HIGH SCHOOL - Козлакова, Г. О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
A review of the scientific and pedagogical heritage of Semen Ustimovich Goncharenkо has been carried out and an assessment of its influence on the development of pedagogical research in domestic higher educational institutions, in particular, in technical universities. The content, form, structure of his works are an example for imitation, and his books are inspired nowadays, help young scientists and cherish the bright memory of the outstanding Teacher, Mentor, Scientist